The inverse source problems for the Helmholtz operators - Luc, Le Trong (Journal of Computer Science and Cybernetics, 2016)
The paper is devoted to studying the inverse source problem for the Helmholtz equations as investigating solution sets (or information content) because of its ill-posedness, consisting of source distributions located on a closed domain considered, which create the potentials known outside that closed domain and unknown on it.